Integral drama : culture, consciousness and identity - Haney, William S. (Consciousness, literature & the arts ;, 2008)
"Integral Drama critically explores modern drama in the context of Indian aesthetics described in the Natyashastra and the vast, new interdisciplinary field of consciousness studies. It also focuses on how Indian theatre aesthetics has influenced modern drama theories and practice, and the extent to which this has promoted the development of higher consciousness in actors and audience. According to Indian aesthetics, rasa or aesthetic rapture is refers to bliss innate in the Self that manifests even in the absence of external sources of happiness. Overall, this book explores the relation between modern theatre and higher states of mind and demonstrates that one of the key purposes of theatre is to help the spectator experience the pure consciousness event described in consciousness studies by theorists such as Anna Bonshek, Ken Wilber, Robert K.C. Forman, Jonathan Shear, Daniel Meyer-Dinkgrafe, Ralph Yarrow and others." "Integral Drama will appeal not only to drama theorists but also to teachers and students of acting, as well as an educated general audience interested in understanding the aesthetic experience of theatre. Integral Drama, moreover, can be used as a textbook for acting and drama theory classes and would also appeal to university and public libraries. The book serves as a bridge between the ideas and experiences long understood through Indian philosophy and the many questions raised by modern theatre studies."--Jacket